2014
DOI: 10.1080/15299732.2014.869144
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean Tsunami: Relationships Among Posttraumatic Stress, Posttraumatic Growth, Resource Loss, and Coping at 3 and 15 Months

Abstract: This study examines variables associated with posttraumatic stress symptoms (PTS) and posttraumatic growth among 2 independent samples of survivors following the Indian Ocean tsunami in Khao Lak, Thailand. Participants were exposed to unprecedented horror and loss of life and property. At 3 months participants (N = 248) were living in temporary shelters, and at 15 months a second sample (N = 255) was living in homes built after the tsunami. Prior traumatic experiences, life threat, loss of personal characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…None of these consequences affected the study group, who were able to fly home a few days after the disaster (Sattler, Assanangkornchai, Moller, Kesavatana-Dohrs, & Graham, 2014). This limits the generalizability of the study while also allowing us to examine and compare different types of exposure in a much more isolated way.…”
Section: Discussionmentioning
confidence: 99%
“…None of these consequences affected the study group, who were able to fly home a few days after the disaster (Sattler, Assanangkornchai, Moller, Kesavatana-Dohrs, & Graham, 2014). This limits the generalizability of the study while also allowing us to examine and compare different types of exposure in a much more isolated way.…”
Section: Discussionmentioning
confidence: 99%
“…Support provided by co‐workers, supervisory personnel and family members may be essential in helping promote and enhance personal characteristic and condition resources (Cowman et al, ; Huynh et al, ). These recommendations may assist firefighters in taking action to resolve feelings of distress, manage emotions, clarify values and life priorities (Calhoun & Tedeschi, ; Janoff‐Bulman, ; Sattler et al, ), and offset—to some degree—negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, firefighters may experience increased awareness of life priorities and positive life changes as a result of thinking about the incident (Groleau, Calhoun, Cann, & Tedeschi, ). They may refine or learn new coping skills, gain an enhanced appreciation for life and experience new levels of self‐efficacy (viz., gain new resources, Linley & Joseph, ; Sattler, Assanangkornchai, Moller, Kesavatana‐Dohrs, & Graham, ). These positive outcomes may offset to some degree negative experiences (Groleau et al, ; Linley & Joseph, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have suggested that early successful coping may lead to later growth (Tedeschi & Calhoun, 2004). In fact, coping was a significant predictor of posttraumatic growth even after accounting for variables, such as social support, past trauma experience, loss of resources, health problems, gender, age, and education (He, Xu, & Wu, 2013;Sattler, Assanangkornchai, Moller, Kesavatana-Dohrs, & Graham, 2014).…”
Section: Discussionmentioning
confidence: 99%